FIRM VALUE: APAKAH BERPENGARUH PADA EKSISTENSI FEMALE BOC DAN FAKTOR LAINNYA - William, Kenneth; Tjahjono, Rudi Setiadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the factors influencing Firm Value. These factors include the existence of the Female Board Commissioner, Tax Avoidance, Dividend Policy, Firm Size, Investment Decision, Leverage, and Profitability. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. Using purposive sampling techniques and after a data selection process based on predetermined criteria, a total of 46 companies met the requirements, resulting in 138 observations. The analysis method employed in this research is multiple linear regression, with data processed using SPSS version 25. The results of this study indicate that Leverage, Profitability, and Investment Decision significantly impact Firm Value. Meanwhile, other independent variables, such as the existence of the Female Board of Commissioner, Tax Avoidance, Firm Size, and Dividend Policy, do not have a significant impact on Firm Value.